2017
DOI: 10.3389/fevo.2017.00096
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Pools as Early Indicators for Soil Organic Matter Stock Changes under Different Tillage Practices in Inland Pacific Northwest

Abstract: Soil organic matter (SOM) is essential for sustaining soil health and crop productivity. However, changes in SOM stocks in response to agronomic practices are slow and show years later when it is too late for adjustments in management. Identifying early indicators of SOM dynamics will allow early management decisions and quick remedial action. The objectives of this study were to evaluate long-term effects of tillage intensity and timing on SOM pools and determine the most responsive SOM pools to tillage pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 54 publications
(150 reference statements)
6
50
2
2
Order By: Relevance
“…The range (0.1-3.5%) in WEOC as a fraction of total C in our soil was generally consistent with previous studies that reported that WEOC generally represents < 4% of the total C or total organic C in agricultural soils (McGill et al 1986;Zsolnay 1996;Angers et al 2006;Hamkalo and Bedernichek 2014;Benbi et al 2015;Awale et al 2017). The percentage values in our study may have been slightly underestimated at deeper depths because of increasing inorganic C. The percentage of WEOC (of total C) in SM and CM with ST bedding is 6 to 7% (Miller et al 2012), and in feedlot manure in southern Alberta it is 6% (Hao et al 2014).…”
Section: Relationship Of Weoc With Total Carbon In Soilsupporting
confidence: 91%
See 1 more Smart Citation
“…The range (0.1-3.5%) in WEOC as a fraction of total C in our soil was generally consistent with previous studies that reported that WEOC generally represents < 4% of the total C or total organic C in agricultural soils (McGill et al 1986;Zsolnay 1996;Angers et al 2006;Hamkalo and Bedernichek 2014;Benbi et al 2015;Awale et al 2017). The percentage values in our study may have been slightly underestimated at deeper depths because of increasing inorganic C. The percentage of WEOC (of total C) in SM and CM with ST bedding is 6 to 7% (Miller et al 2012), and in feedlot manure in southern Alberta it is 6% (Hao et al 2014).…”
Section: Relationship Of Weoc With Total Carbon In Soilsupporting
confidence: 91%
“…Positive and significant correlations (r=0.76 to 0.80) have been reported between WEOC and total organic C in arable soils (Hamkalo and Bedernichek 2014;Haney et al 2014;Awale et al 2017). But some have reported poor correlations (r=0.24) in other arable soils (Benbi et al 2015).…”
Section: Relationship Of Weoc With Total Carbon In Soilmentioning
confidence: 95%
“…Furthermore, Hedley et al [2] reported that conversion of perennial pasture over time accumulates more C in the soil than the annually cultivated pasture. The protected SOM becomes more accessible to the soil microbes, and the soil environment becomes more conducive to SOM mineralization under cropland than in undisturbed pasture, increasing the probability of C and N loses in cultivated soils [3]. The loss of nutrients becomes more severe in dryland wheat-fallow cropping systems of the PNW because fallowing keeps the soil moist in the summer which permits greater biological oxidation than would normally occur [1].…”
Section: Soil Macronutrients After 75 Years Of Tillage and N Fertilizmentioning
confidence: 99%
“…Tillage affects SOM [3], pH [4], and nutrient availability [5]. Conservation tillage, such as disc plow (DP) and sweep (SW), have shown positive effects on crop productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although intensive cultivation of Bt-cotton might add increased biomass to the soil, a negative C and N balance might occur due to rapid depletion of nutrients in such systems (Sarkar et al 2008;Beura & Rakshit 2011). Further, intensive cultivation under mechanized farming cause rapid changes in native ecosystems that might cause easy oxidation of soil organic C (Awale et al 2017).…”
Section: Introductionmentioning
confidence: 99%